Chicken Organic Anion-Transporting Polypeptide 1A2, a Novel Avian Hepatitis E Virus (HEV) ORF2-Interacting Protein, Is Involved in Avian HEV Infection - Li, Huixia (J Virol, 2019)
Avian hepatitis E virus (HEV) is the main causative agent of big liver and spleen disease in chickens. Due to the absence of a highly effective cell culture system, there are few reports about the interaction between avian HEV and host cells. In this study, organic anion-transporting polypeptide 1A2 (OATP1A2) from chicken liver cells was identified to interact with ap237, a truncated avian HEV capsid protein spanning amino acids 313 to 549, by a glutathione S-transferase (GST) pulldown assay. GST pulldown and indirect enzyme-linked immunosorbent assays (ELISAs) further confirmed that the extracellular domain of OATP1A2 directly binds with ap237. The expression levels of OATP1A2 in host cells are positively correlated with the amounts of ap237 attachment and virus infection. The distribution of OATP1A2 in different tissues is consistent with avian HEV infection in vivo. Finally, when the functions of OATP1A2 in cells are inhibited by its substrates or an inhibitor or blocked by ap237 or anti-OATP1A2 sera, attachment to and infection of host cells by avian HEV are significantly reduced. Collectively, these results displayed for the first time that OATP1A2 interacts with the avian HEV capsid protein and can influence viral infection in host cells. The present study provides new insight to understand the process of avian HEV infection of host cells. IMPORTANCE The process of viral infection is centered around the interaction between the virus and host cells. Due to the lack of a highly effective cell culture system in vitro, there is little understanding about the interaction between avian HEV and its host cells. In this study, a total of seven host proteins were screened in chicken liver cells by a truncated avian HEV capsid protein (ap237) in which the host protein OATP1A2 interacted with ap237. Overexpression of OATP1A2 in the cells can promote ap237 adsorption as well as avian HEV adsorption and infection of the cells. When the function of OATP1A2 in cells was inhibited by substrates or inhibitors, attachment and infection by avian HEV significantly decreased. The distribution of OATP1A2 in different chicken tissues corresponded with that in tissues during avian HEV infection. This is the first finding that OATP1A2 is involved in viral infection of host cells.